1992
DOI: 10.1007/978-1-4899-1648-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Complications of Cocaine Abuse

Abstract: Abstract. Upper respiratory and pulmonary complications of cocaine addiction have been increasingly reported in recent years, with most of the patients being intravenous addicts, users of freebase, or smokers of "crack."The toxicity of cocaine is complex and is exerted via multiple central and peripheral pathways. Recurrent snorting of cocaine may result in ischemia, necrosis, and infections of the nasal mucosa, sinuses, and adjacent structures.Pulmonary complications of cocaine toxicity include pulmonary edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Epidemiologic studies have consistently found that cigarette smoking is a risk factor for both carriage and invasive disease and that the common mechanism may be damage to the respiratory mucosa. Similarly, inhalation of cocaine damages the respiratory tract mucosa and may facilitate invasion [17]. Furthermore, both opiates and marijuana have been implicated as immunosuppressors in humans and animals [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have consistently found that cigarette smoking is a risk factor for both carriage and invasive disease and that the common mechanism may be damage to the respiratory mucosa. Similarly, inhalation of cocaine damages the respiratory tract mucosa and may facilitate invasion [17]. Furthermore, both opiates and marijuana have been implicated as immunosuppressors in humans and animals [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that this abrupt decrease in CBFv interferes with the buffering capacity of the vascular system to compensate for regional hypoperfusion. Indeed, abrupt perturbation of CBF can trigger symptom presentation in vascular diseases in other organs, such as lung and heart (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Through inhalation, these drugs can damage respiratory mucosa and increase susceptibility to meningococcal disease ( 10 ). In addition, drug use can be a social activity involving equipment sharing among users, thus increasing respiratory secretion exposure.…”
Section: Discussionmentioning
confidence: 99%